Implementasi Interprofesional Colaboration Melalui Clinical Meeting Terhadap Kepuasan Keluarga Pasien Ruang Rawat Inap Rumah Sakit Semarang - Imrotun; Fery Agusman Metuho Mendrofa; Shindi Hapsari; Susi Nurhayati (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: Satisfaction is one of the indicators of hospital services, especially the satisfaction given by patients and families. The existence of data on high-risk inpatients in the Intensive Care room with the high-risk, high volume, and high-cost categories in July 2023 amounted to 45 cases, August 52 cases, September 39 cases, so it requires the implementation of Interprofessional Collaboration through clinical meetings on the satisfaction of patient families in the Inpatient Room of Telogorejo Hospital Semarang. Methods: The research method was carried out as a quasi-experiment on 20 people in the treatment group who were given clinical meetings and 20 people in the control group who were given family education. Data were analyzed from the questionnaire instrument using Wilcoxon and Mann-Whitney. Results: The results showed that there was a difference in family satisfaction after a clinical meeting with a p-value of 0.003 and there was a difference in family satisfaction after being given family education with a p-value of 0.004. In the analysis of the two groups, there was an influence on the implementation of interprofessional collaboration through clinical meetings and family education with a p-value of 0.001. Discussion: Intense exposure to gadgets has limited stimulus and optimization of social development. Therefore, synergy between the school and parents in establishing policies regarding the use and supervision of gadgets is needed, as an effort to prevent the use of gadgets from replacing direct social interactions that are essential for children's development.